Electronic Human Resource Management Practices, Information Technology Capability and Organisational Performance: A Review Paper Toward Conceptual Framework - et.al, Naji Mohammad Awwad Alrawashdeh, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This paper provides a conceptual framework for studying the influence of Electronic Human Resource Management practices and information technology capability on organisational performance. This paper aims to increase our understanding of the organisational performance as the phenomenon focus on that is considered the dependent variable, the e-HRM practices are the independent variables, and IT capability is the moderating variable. Such conceptual framework can provide guidance for future research to help in the identification, realisation and assessment of e-HRM implementation benefits. Special focus is put on organisational performance. Moreover, this conceptual framework complements and continues former literature and presents a new delineated framework for considering research on e-HRM practices influence on organisational performance. This conceptual framework will be our empirical study in the future, which will contribute to HRM literature and determines the potency of e-HRM and its effect on organisational performance.